Estrutura cristalográfica da BnIV, uma miotoxina de Bothrops neuwiedi - Souza, Emmanuel Prata de (2007)
Phospholipases A2 (PLA2) are enzymes that convert a phospholipid in a free fat acid and a lisophospholipid at the sn-2 position. There are several sources to PLA2, which can be citosolic or secreted. For the secreted PLA2, there are proteins with D49 and others with K49 residue [...]